(3cJGH GdCdaGX GdaGNQI aj Pe GdOfjG heOM GdBNQIs
(3ChdgG (B:s
(3GdMeO ddg GdPi EYdfcSJ GdXdeGA HbOQJg hGYThTJ GdHjOGA HQMeJg CeG HYO aEf GaVd GdcdGe GfaYg hGTQa GdfXGe GQaYg hGdfUjMI QCS GdOjGfg s
(3BNQgG (B:s
(3jfJgi HOYGA GNQg hdG JMedfG ahb WGbJfG hGMedfG hYGafG hGYa YfG hGJfG ai GdOfjG MSfI hai GdGNQI MSfI hbfG YPGH GdfGQ HQMeJc jG GQMe GdQGMejf Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs